PEMANFAATAN APLIKASI ENGLISH PRONOUNCER UNTUK PENGAJARAN MATA KULIAH SPEAKING I MAHASISWA SEMESTER II PRODI PENDIDIKAN BAHASA INGGRIS STKIP YPM BANGKO - Diyan Andriani; Sri Utaminingsih (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
The speaking ability of first semester students with good pronunciation was still low. Therefore, in Semester II there needs to be an effort to overcome this problem, namely by using mobile learning based on Android smartphones using the